SAT0622 High dose intravenous methylprednisolone induces rapid improvement in severe uveitis: a multicenter study of 129 patients. (12th June 2018) - Vegas-Revenga, N.; Calvo-Río, V.; González-Mazón, I.; Sánchez-Bilbao, L.; Beltrán, E.; Follonosa, A.; Maíz, O.; Blanco, A.; Cordero, M.; Ortego, N.; Torre, I.; Hernández, F.; et al.
Abstract : Background: In uveitis rapid and effective remission-inducing therapy is mandatory to avoid irreversible damage. Objectives: To evaluate the efficacy and safety of high-dose intravenous methylprednisolone (IVMP) pulse therapy in uveitis. Methods: Multicentre study of 129 patients (203 eyes) with uveitis who received IVMP. The underlying diseases were: Idiopathic (n=30), Vogt Koyanagy Harada, 29 Behçet disease, 19 Sarcoidosis, 6 Multifocal Choroidopathy, 4 Birdshot chorioretinopathy, 2 Acute posterior multifocal placoid pigment epitheliopathy, 1 Granulomatosis with polyangiitis, 2 Aortitis, 1 Immune thrombocytopenic purpura, 1 Rheumatoid arthritis, 2 Axial Spondylitis, 6 Psoriatic arthritis, 2 Juvenile Idiopathic Arthritis, 1 Thrombophilia synd., 1 Eales Disease, 2 Sympathetic Ophthalmia, 2 Multiple Sclerosis, 2 Relapsing Polychondritis, 1 Cogan's synd., 1 Sjögren synd., 2 Crohn's disease, 1 Reactive arthritis, 1 Toxic oil synd. and brain ischemia, 1 Raynaud's Disease and brain ischemia, 1 Pseudotumor, 1 Cataract surgery, 1 Herpes Simplex, 1 Varicella Zoster- associated acute retinal necrosis, 1 T.pallidum 3 and M.tuberculosis . 1 The inflammatory ocular patterns were: panuveitis (66), posterior uveitis (PU), 31 intermediate uveitis (IU), 5 anterior uveitis (AU), 12 AU and PU, 2 AU and IU, 1 IU and PU, 1 exudative retinal detachment, 3 vasculitis, 4 pseudotumor, 1 scleritis 2 and sclero-uveitis. 1 Bilateral ocular involvement was observed in 74 cases. Patients were assessed at basal visit and day 2–5, 7, 15 and 30 after IVMP. The main outcome variable was best corrected visual acuity (BCVA), the degree of inflammation of the anterior chamber and vitreous, and macular thickness (macular oedema defined by OCT >300 µm). The results are expressed as mean ±SD for normally distributed variables, or as median [interquartile range] when are not. Comparison of continuous variables was performed using the Wilcoxon test. Results: We studied 74 &x2640;/55 &x2642;; mean age 42±14.3 years. IVMP dose ranged from 40–1000 mg/day for 3–5 consecutive days. Prior to IVMP, cycloplegic and corticosteroid eye drops were used in all cases. Improvement was faster among patients with inflammation in anterior chamber and vitritis than in BCVA, CME, retinitis and retinal vasculitis (TABLE) . Total remission was achieved in 19.4% of the 129 patients after IVMP. In 126 of the patients continued with oral corticosteroids and 4 received an intraocular dose of steroids. These immunosuppressive drugs were added: Methotrexate (52), Cyclosporine A, 48 Azathioprine 40 and others. 5 In a few cases biological therapy (64) was administered afterwards. In general, acute respiratory infection was the side-effect most frequent. Conclusions: High-dose IVMP pulse therapy is beneficial in the prompt control of severe uveitis and it is well tolerated. Disclosure of Interest: None declared